Communication dynamics and media interactions of young adults who have attempted suicide: a qualitative thematic analysis - Arık, Emel; İnce, Mustafa; Koçak, Mevlüt Can; Bilişli, Yasemin; Karataş, Emrah Onur; Akgün, Hakkı; Aşlakçı, Faruk (Frontiers in Psychology, 2024)
The study examines the potential effects of communication processes and media consumption habits on suicide ideation among male and female young adults aged 18-29 who have attempted suicide at least once.In-depth interviews were analyzed using MAXQDA Analytics Pro 2024, and thematic analysis was applied according to Braun and Clarke's model.Results: Four themes emerged: (1) Family-related factors, (2) sociopsychological factors, (3) sociocultural factors, and (4) media-related factors. Regarding family-related factors, most participants come from broken family structures and commonly report issues with family communication and experiences of violence. Regarding sociopsychological factors, anger issues, despair, and addictions among participants were observed to increase suicide tendencies. Regarding sociocultural factors, most participants expressed difficulties in conforming to society and feeling pressures from cultural or religious expectations. Regarding media-related factors, it was noted that a vast majority of participants spend long hours consuming media daily and frequently interact with content that leads them into adverse emotional states, primarily for time passing on social media platforms.Discussion: This research not only reinforces information in the literature but also presents unique findings compared to similar studies, particularly in cultural and geographical contexts. The results uniquely highlight the diversity in perceptions of the relationship between religion and suicide. While literature generally notes religion as a deterrent to suicide, this study reveals that intense religious pressure could increase suicidal tendencies through effects like rejection and hatred of religious values. Media also plays a reinforcing role in this context.In conclusion, this study elucidates the complex interactions underlying suicide attempts among young adults and provides a solid foundation for policies and interventions aimed at better managing media interactions, which play a critical role in suicide prevention efforts.